Sustainability awareness, management practices and organisational culture in hotels: Evidence from developing countries - Oriade, Ade; Osinaike, Adesola; Aduhene, Ken; Wang, Yong (International journal of hospitality management, 2021)
The subject of sustainability and it its management in the hotel context is somewhat volatile with varied evidence in support of different viewpoints. This study, adopting Situated Cognition (SC), explores the role of organisational culture in sustainability practice and awareness among hotel practitioners. The findings from this study reveal that management practice of sustainability has strong relationship with both organisational culture and employees’ sustainability awareness. However, organisational culture only mediates the relationship between sustainability awareness and management on country to country basis. The study recommends that owner-managers need to realise the importance of building up a robust organisational culture particularly in support of their sustainability management and empowerment of their staff.